Curriculum Evaluation of English Course of Bachelor of Business Studies (BBS) of Tribhuvan University - Bastola , Ganesh Kumar (Journal of Management, 2024)
The study has explored the existing Bachelor in Business Studies (BBS) English curriculum of Tribhuvan University. The existing English curriculum at the Bachelor of Business Studies tends to teach the basics of grammar, communicative functions for business, and some literary constructs to help students connect their understanding of their learning. English is taught in the first and the second year of a year’s bachelor's program in the management faculty. Having a profound focus on the communicative aspect of business, the English curriculum intends to improve linguistic competence at lexical, structural and grammatical levels. The English curriculum opts for producing correct sentences, cohesive paragraphs, and organized texts on one hand and responding to literary and business readings critically and analytically on the other. In a broader sense, the curriculum tends to boost competence towards global understanding thereby strengthening their confidence. The students are expected to learn prior understanding, develop analytical and interpreting skills and enhance better communicative competence and business skills. However, the learners are taught to be capable enough to create new insight through critical reading, rationalizing grammatical assets and employing them in their real-life situations. Thus, this curriculum tries to cover the contemporary needs of both the learners and the society to serve the purpose of the 21st century.